Guerrilla marketing for job hunters 3.0 : how to stand out from the crowd and tap into the hidden job market using social media and 999 other tactics today - Levinson, Jay Conrad; Perry, David, 1960 Jan. 12- (Hoboken, N.J. : Wiley, 2011)
'Guerrilla Marketing for Job Hunters-3rd edition will be revised, updated, and expanded to include new and timely information about recruiting in the information age. This will be specific to utilizing social networking tools as a means of taking control of the job search, as well as expert advice from respected guest bloggers. In short, the 3rd edition expands on the techniques of the 2nd edition, including tips on how to Leverage Facebook, Twitter, Google, and other social networking sites to take advantage of'the secret lives of top recruiters' Learn how to present their skills in creative new ways that stand out in today's hyper-competitive job market Employ little-known search engine optimization tricks used by top headhunters'--
Includes index.
Keywords: Job hunting; Social media; Career development; Vocational guidance